Scientific Merits and Analytical Challenges of Tree‐Ring Densitometry. (26th November 2019) - Björklund, J.; von Arx, G.; Nievergelt, D.; Wilson, R.; Van den Bulcke, J.; Günther, B.; Loader, N. J.; Rydval, M.; Fonti, P.; Scharnweber, T.; Andreu‐Hayles, L.; Büntgen, U.; et al.
Abstract: X‐ray microdensitometry on annually resolved tree‐ring samples has gained an exceptional position in last‐millennium paleoclimatology through the maximum latewood density (MXD) parameter, but also increasingly through other density parameters. For 50 years, X‐ray based measurement techniques have been the de facto standard. However, studies report offsets in the mean levels for MXD measurements derived from different laboratories, indicating challenges of accuracy and precision. Moreover, reflected visible light‐based techniques are becoming increasingly popular, and wood anatomical techniques are emerging as a potentially powerful pathway to extract density information at the highest resolution. Here we review the current understanding and merits of wood density for tree‐ring research, associated microdensitometric techniques, and analytical measurement challenges. The review is further complemented with a careful comparison of new measurements derived at 17 laboratories, using several different techniques. The new experiment allowed us to corroborate and refresh "long‐standing wisdom" but also provide new insights. Key outcomes include (i) a demonstration of the need for mass/volume‐based recalibration to accurately estimate average ring density; (ii) a substantiation of systematic differences in MXD measurements that cautions for great care when combining density data sets for climate reconstructions; and (iii) insights into the relevance of analytical measurement resolution in signals derived from tree‐ring density data. Finally, we provide recommendations expected to facilitate futureinter‐comparability and interpretations for global change research. Plain Language Summary: Paleoclimatology, the study of how the climate has changed throughout earth history, is an important component of climate change research. The wood density of tree rings is a widely used parameter to study past temperature changes. Despite wood density being widely used and considered excellent for this type of research, deriving comparable measurements at different laboratories and using a variety of techniques are proving challenging. This review compiles the current understanding and merits of wood density as a proxy in paleoclimate research. We further describe and review prevalent measurement techniques and associated analytical measurement challenges. The review is also complemented with a careful comparison of a set of new measurements derived at 17 laboratories, using several different techniques. We find that there are substantial differences in measurements performed among laboratories. The main challenge is associated with the analytical resolution when measuring small features such as the density of the latewood. We provide recommendations for future work to overcome systematic differences and towards the prospect of combining measurements from different techniques in integrative studies. Key Points: We review the merits and state of the art of tree‐ring wood microdensitometry and its associated analytical challenges We show that systematic level offsets in mean wood density from different techniques and laboratories require correction Measurement resolution—notoriously difficult to control—is identified as the major challenge for future research applications